The Influence of Environmental Performance, Risk Minimization, Firm Size, Public Share Ownership, and Audit Committee on Corporate Social Responsibility (CSR) Disclosure - Maharani, Risda Lalita; Trisnawati, Rina; Pusparini, Nandya Octanti (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study aims to examine the influence of environmental performance, risk minimization, firm size, public share ownership, and audit committee on Corporate Social Responsibility (CSR) disclosure. The measurement of Corporate Social Responsibility is felt in the global reporting initiatives (GRI)-G4 index which is seen from the company's annual report. Methodology: This research adopts a quantitative approach. The population of the study consists of industrial sector companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2022. The sampling technique used is purposive sampling and got 13 companies, with 4 years observation. So the total sample studied is 52 data. Data analysis was performed using SPSS. The data have been collected analyzed by using the classical assumption test and then tested the hypothesis by multiple linear regression methods with the F test, coefficient of determination, and t-test. Results: This study reveals that firm size and audit committee variables have a significant effect on CSR disclosure. Meanwhile, environmental performance, risk minimization, and public share ownership variables do not have a significant effect on CSR disclosure. Applications/Originality/Value: Corporate Social Responsibility (CSR) is a form of environmental and social responsibility performed by the company to their stakeholders due to the impact of operating activities. CSR information disclosed in the annual report is still not specific because the social responsibility disclosure policy in Indonesia is still voluntary, so in the practice there is still a lot of variability in the breadth of items disclosed and issues arise due to companies that are not taking CSR activities seriously. Therefore, this research is expected to be a guide for policy makers in making regulations and companies as actors of CSR activities to pay more attention to the social and environmental impacts of business activities and disclose them transparently.